2012
DOI: 10.1586/eop.12.56
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolds and stem cells: delivery of cell transplants for retinal degenerations

Abstract: Retinal degenerations and optic neuropathies often lead to death of photoreceptors or retinal ganglion cells, respectively. Stem cell therapies are showing promise for these diseases in preclinical models and are beginning to transition into human trials, but cell delivery and integration remain major challenges. Focusing on photoreceptor- and progenitor-directed approaches, in this article, the authors review how advances in tissue engineering and cell scaffold design are enhancing cell therapies for retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 73 publications
(68 reference statements)
1
45
0
Order By: Relevance
“…Evidence has shown that using a polymer scaffold could offer better manipulation of the extracellular environment and afford the most appropriate degree of cell attachment, differentiation, and maintenance of apposite function (Tomita et al, 2005;Kador and Goldberg, 2012;Kundu et al, 2014). Current ongoing preclinical trials are applying various types of scaffolds for monolayer stem cells transplantation.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Evidence has shown that using a polymer scaffold could offer better manipulation of the extracellular environment and afford the most appropriate degree of cell attachment, differentiation, and maintenance of apposite function (Tomita et al, 2005;Kador and Goldberg, 2012;Kundu et al, 2014). Current ongoing preclinical trials are applying various types of scaffolds for monolayer stem cells transplantation.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…[12] However, RGC transplantation is inherently more difficult than photoreceptor transplantation, as it requires the transplanted cells to integrate dendritically with their amacrine or bipolar cell presynaptic partners in the inner plexiform layer, extend their axons radially through the retina to the optic nerve, grow down the optic nerve and find their appropriate targets in the brain. Previously, we investigated the use of both PLL-PEG hydrogels [26] and PLA electrospun scaffolds [27] to study RGC survival and neurite growth and as a potential cell delivery vehicle. Unlike hydrogels, PLA electrospun scaffolds allowed RGC axons to replicate the radial organization of native RGCs in the retina, but they did not promote the polarization or centripetally directed growth seen in the retina in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we propose that a well-characterized 3D tissue-engineered retina will provide many advantages in cost, animal usage, and assay specificity for programs interested in gene or drug screening. Finally, it will be a major step forward in cell replacement therapies currently being studied, to develop a 3D neural tissue platform as a starting point to study tissue/organ replacement therapy for the eye or brain, enhancing our understanding of the basic mechanisms of neuronal integration in these approaches, rebuilding neural circuitry in vitro , and replacing whole circuits in vivo [29]. …”
Section: Discussionmentioning
confidence: 99%